Penggunaan Aplikasi Quizizz sebagai Media Pembelajaran pada Mata Pelajaran Fiqih di MA Daarul Qur’an Kecamatan Klari Karawang - Aulia Nurpratiwi; Achmad Junaedi Sitika; Debibik Nabilatul Fauziah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Along with the development of technology, there are many updates in the use of learning media, one of wich is by using the Quizizz Application. Quizizz is an online based educational game application that can be used as a means of delivering learning materials and as a learning evaluation medium. Where Quizizz has interesting features that make learning more fun. The Quizizz application is one of the choices of learning media applied by Fiqh teachers at MA Daarul Qur’an because applying it has a better impact on the learning process. This research uses descriptive qualitative methods with data sources including observation, interviews with Fiqh teachers and vice principals in the field of curriculum and serval students. The results of the study prove that the use of the Quizizz application in Fiqh subjects at MA Daarul Qur’an from the planning, implementation, to evaluation stages is carried out well. This can be seen from the students understanding of the material provided is increasing. As for the use of the Quizizz application, there are supporting factors including: an application that is easily accessible, the use of quotas is not much, there is an element of competition, presents a variety of questions, and the school provides several facilities. The inhibiting factors in using the Quizizz application are: the internet network is often weak, the number of computers in not large, and it takes more time.